Anxiety, Depression and Sexual Dysfunction in the Patients Undergoing Bone Marrow Transplantation - Mohammadi Ali (Journal of Global Pharma Technology, 2017)
Introduction nowadays, following improvement in bone marrow transplantation (BMT) techniques, and increase in life expectancy in patients whom undergoing this procedure, researchers have paid attention toward improvement in quality of life of these patients. Some of the most important problems of these patients include anxiety, depression and sexual dysfunction. Considering that there are few studies regarding the prevalence of these disorders and its related factors and because of controversy in their results, and lack of any study in this topic in Iran, this study was performed. Material and Method: This study was a cross sectional study and the sampling method was simple sampling method. The studied community was 60 patients who were received BMT and referred to oncology clinic of Taleghani hospital in Tehran. The inclusion criteria were receiving BMT from 3 months to 3 years, and having consent for participation in the study. The exclusion criteria were not having consent for participation in the study, and the age under 18 years. The study tools were three questionnaires: Persian version of hospital anxiety and depression scale (HADS) and Arizona Sexual Experience Scale (ASEX) both were standardized previously; and a questionnaire regarding demographic data of participants and other needed data such as history of anxiety, depression and sexual dysfunction prior to BMT, type of primary disease, and type of performed BMT that were extracted from the patient’s records. After data gathering, the data was analyzed using SPSS software version 22 and using general indexes of descriptive statistics, qui-square and t-test. Results 25 participants were female and 35 men. The rate of anxiety, depression and sexual dysfunction prior to BMT were 21(35%), 10(16.7%) and 16(26.7%) respectively and after BMT were 7(11.7%), 6(10%) and 38(63.3%) respectively. The increase in sexual dysfunction after BMT was statistically significant. (p=0.024) Conclusion the rate of sexual dysfunction may increase after BMT.Keywords: Bone marrow transplantation, Anxiety, Depression, Sexual dysfunction.